2006
DOI: 10.1007/s11218-006-9003-x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural values in the home and school experiences of low-income African-American students

Abstract: The present study examined the presence of specific cultural values within the preferred classroom and home activities of African-American upper elementary students. Written scenarios were constructed and used to determine whether students preferred their home and classroom activities carried out under specific cultural terms. Students also reported their perceptions of teachers and parents' cultural value-based preferences for classroom and home activities. With analysis of variance techniques, it was shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…The examination of parenting strategies in the current sample adds to a very limited body of research, as less attention has been given to family factors that influence academic achievement in African American children (Mandara, 2006;Taylor & Lopez, 2005). Burgeoning research focuses on the link between parenting and school outcomes to understand academic achievement disparities in low-income and ethnic minority children (Taylor & Lopez, 2005;Tyler, Boykin, Miller, & Hurley, 2006). One area of debate is the question of the types of parental strategies that are most beneficial for low-income, African American children (Connell & Prinz, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The examination of parenting strategies in the current sample adds to a very limited body of research, as less attention has been given to family factors that influence academic achievement in African American children (Mandara, 2006;Taylor & Lopez, 2005). Burgeoning research focuses on the link between parenting and school outcomes to understand academic achievement disparities in low-income and ethnic minority children (Taylor & Lopez, 2005;Tyler, Boykin, Miller, & Hurley, 2006). One area of debate is the question of the types of parental strategies that are most beneficial for low-income, African American children (Connell & Prinz, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This refers to learning preferences for visual, auditory, tactile, and motor channels simultaneously; rhythmic and creative behavior; and a simultaneous focus on multiple concerns rather than only one . African American parents and children prefer cultural value‐based communal and vervistic activities in home and school settings over individualistic and competitive practices reflective of mainstream values . Exposure to culturally matched strategies enhances academic performance .…”
Section: Cultural Considerationsmentioning
confidence: 99%
“…For example, African American parents and their school-age children have reported that communalism, verve, and movement are relatively absent from public school classrooms (Tyler, Boykin, Miller, et al, 2006). Similarly, teachers also have reported or are perceived to endorse mainstream classroom learning behaviors significantly more than cultural value-based behaviors such as communalism or verve (Tyler, Boykin, Miller, et al, 2006).…”
Section: Research Support For Communalism Movement and Verve Among mentioning
confidence: 99%